Sickle cell disease chronic joint pain: Clinical assessment based on maladaptive central nervous system plasticity - Lopes, Tiago da Silva; Ballas, Samir K.; Santana, Jamille Evelyn Rodrigues Souza; de Melo-Carneiro, Pedro; Oliveira, Lilian Becerra de; Sá, Katia Nunes; Lopes, Larissa Conceição Dias; Silva, Wellington dos Santos; Lucena, Rita; Baptista, Abrahão Fontes (Frontiers in Medicine, 2022)
Chronic joint pain (CJP) is among the significant musculoskeletal comorbidities in sickle cell disease (SCD) individuals. However, many healthcare professionals have difficulties in understanding and evaluating it. In addition, most musculoskeletal evaluation procedures do not consider central nervous system (CNS) plasticity associated with CJP, which is frequently maladaptive. This review study highlights the potential mechanisms of CNS maladaptive plasticity related to CJP in SCD and proposes reliable instruments and methods for musculoskeletal assessment adapted to those patients. A review was carried out in the PubMed and SciELO databases, searching for information that could help in the understanding of the mechanisms of CNS maladaptive plasticity related to pain in SCD and that presented assessment instruments/methods that could be used in the clinical setting by healthcare professionals who manage chronic pain in SCD individuals. Some maladaptive CNS plasticity mechanisms seem important in CJP, including the impairment of pain endogenous control systems, central sensitization, motor cortex reorganization, motor control modification, and arthrogenic muscle inhibition. Understanding the link between maladaptive CNS plasticity and CJP mechanisms and its assessment through accurate instruments and methods may help healthcare professionals to increase the quality of treatment offered to SCD patients.